2001
DOI: 10.1620/tjem.194.137
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Maternal Peripheral T Helper 1-Type and T Helper 2-Type Immunity during Labor.

Abstract: The percentages of Th1 and Th2 cells and the Th1:Th2 ratios in peripheral blood from 22 patients with a singleton pregnancy at 30 and 36 weeks' gestation, on admission for the spontaneous onset of labor pains, at 1 minute after placental delivery and on day 7 after delivery were determined using flow cytometry. The percentages of Th1 and Th2 cells and the ratio of Th1:Th2 did not markedly change during 30 weeks' gestation and 1 minutes after placental delivery. However, the percentage of Th2 cells had decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Labour is often seen as a proinflammatory state marking the end of the pregnancy, and thus it is plausible that labour is associated with a reversal in the bias back towards Th1 rather than Th2. Rather, Kuwajima and colleagues have shown that the Th2:Th1 ratio remained constant in favour of Th2 through pregnancy and labour, with a reversal back to nonpregnant parameters at 7 days postpartum [67]. However, this finding is somewhat contrary to an earlier report indicating that serum IL-4 levels measured by ELISA in women through pregnancy and at different stages of labour were reduced in the later part of labour and by day 1 postpartum in both normotensive and preeclamptic women [68].…”
Section: Th1:th2 Cytokines In Labourmentioning
confidence: 99%
“…Labour is often seen as a proinflammatory state marking the end of the pregnancy, and thus it is plausible that labour is associated with a reversal in the bias back towards Th1 rather than Th2. Rather, Kuwajima and colleagues have shown that the Th2:Th1 ratio remained constant in favour of Th2 through pregnancy and labour, with a reversal back to nonpregnant parameters at 7 days postpartum [67]. However, this finding is somewhat contrary to an earlier report indicating that serum IL-4 levels measured by ELISA in women through pregnancy and at different stages of labour were reduced in the later part of labour and by day 1 postpartum in both normotensive and preeclamptic women [68].…”
Section: Th1:th2 Cytokines In Labourmentioning
confidence: 99%
“…However, this may be no problem because we have observed that the percentage of Th1 and Th2 cells and the ratio of Th1:Th2 do not change markedly during 30 weeks' gestation and 1 min after placental delivery in singleton pregnancies [12].…”
Section: Discussionmentioning
confidence: 83%
“…During labor, the body experiences a pro-inflammatory state, potentially leading to a reversal in immune profile from a Th2-supported state in pregnancy to a Th1 state. However, some studies indicate that the Th2-predominant environment persists throughout labor and only returns to a nonpregnant balance about a week after giving birth 35 . Thus, our findings suggest that HIV-uninfected individuals in labor may exhibit a shift back towards a Th1 response, while PPHIV in our study may not have fully completed this shift.…”
Section: Discussionmentioning
confidence: 99%